Ecotourism and Art Mangunan Kaki Langit Tourism Village - Anwar Yahya, Fahmi; Khairune Nisa, An Nuur; Bahri, Iswan; Oktaviani Gustiarti, Putrisari (Jurnal Toursci, 2023)
Mangunan Kaki Langit Tourism Village is an ecotourism that focuses on community empowerment. The village was formed on March 9, 2014, by the Mangunan Dukuhan KKLPMD Organization. The name "Skyline" has a deep meaning as a symbol of the goal of community empowerment in the Skyline. The concept refers to the idea that the Skyline Tourism Village must be able to move the community to achieve goals without space and time limits by creating new opportunities as a source of income and people's economic empowerment. This study aims to explore the potential of community empowerment of Kaki Langit Tourism Village and evaluate eight main activities that become a forum for community empowerment under their respective fields, such as traditional homestays, traditional culinary, cultural arts, unique tourist accommodation, youth support, local artisans, rural nature education, and agriculture. This research method uses a qualitative approach with data collection techniques through participatory observation, interviews with related parties, and document analysis related to the Skyline Tourism Village. The collected data is analyzed descriptively to get a comprehensive picture of the potential for community empowerment in the village.